Visual evoked potentials in Negro carriers of the gene for tyrosinase positive oculocutaneous albinism. Issue 12 (December 1988) - Castle, D; Kromberg, J; Kowalsky, R; Moosa, R; Gillman, N; Zwane, E; Fritz, V
Abstract : Visual evoked potential testing was performed on 15 Negro carriers of the gene for tyrosinase positive oculocutaneous albinism in order to detect whether they have the same visual pathway decussation anomalies as do homozygotes. No subject showed 01-02 asymmetry on monocular testing, indicating that decussation follows the normal pattern. It is concluded that visual evoked potential testing is probably not useful in the detection of Negroes heterozygous for the gene for tyrosinase positive oculocutaneous albinism.